(untitled) (Journal of the Sociology and Theory of Religion, 2025)
This is a review of a book on the study of human sacrifices in the ancient world. It begins with an approach to the origin of the sacred, to later slide into human sacrifice and ritual magic. To introduce us to the sacrifice of the sacred king, some issues already analyzed in a text by the same author. It continues with theophagy and the mysticism of the Eucharist. It speaks to us of sacred prostitution, a world that was already a common dimension in several cultures in ancient times. And ending with the exploration of human purification, atonement and redemption in the archaic world.